2022
DOI: 10.3758/s13423-022-02122-z
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements dissociate between perceiving, sensing, and unconscious change detection in scenes

Abstract: Detecting visual changes can be based on perceiving, whereby one can identify a specific detail that has changed, on sensing, whereby one knows that there is a change but is unable to identify what changed, or on unconscious change detection, whereby one is unaware of any change even though the change influences one's behavior. Prior work has indicated that the processes underlying these different types of change detection are functionally and neurally distinct, but the attentional mechanisms that are related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, speeding responses in a binary response working memory task leads the linear ROCs to shift toward the chance diagonal (Yonelinas & Jacoby, 1995a; Figure 6c), suggesting that the proportion of items that are recollected depends critically on the processes that unfold during retrieval. In addition, in a recent working memory study for scenes, we found that perceiving-based working memory responses, but not sensing-based responses, depend critically on the subjects fixating on a region at study and then re-fixating on that changed region at time of retrieval (Ramey et al, 2022; also see Henderson & Hollingworth, 1999). These re-fixation results suggest that whether recollection contributes to WM performance depends critically on how attention is deployed during both encoding and retrieval.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In addition, speeding responses in a binary response working memory task leads the linear ROCs to shift toward the chance diagonal (Yonelinas & Jacoby, 1995a; Figure 6c), suggesting that the proportion of items that are recollected depends critically on the processes that unfold during retrieval. In addition, in a recent working memory study for scenes, we found that perceiving-based working memory responses, but not sensing-based responses, depend critically on the subjects fixating on a region at study and then re-fixating on that changed region at time of retrieval (Ramey et al, 2022; also see Henderson & Hollingworth, 1999). These re-fixation results suggest that whether recollection contributes to WM performance depends critically on how attention is deployed during both encoding and retrieval.…”
Section: Discussionmentioning
confidence: 83%
“…The selective relationships between the intercepts and curvilinearity of ROCs on the one hand, and the mental states of perceiving and sensing on the other, indicates that the contents of working memory are available to conscious awareness; but in addition, they suggest that subjects can distinguish between two different types of conscious experience. Whether these two types of responses can be further differentiated from truly unconscious processes is not yet known (although see Ramey et al, 2022). In either case, the existing results indicate that subjects have conscious access to at least some of the processes underlying WM (Fechner, 1887; James, 1890), but points to the importance of distinguishing between cases in which the subjects have conscious access to the specific details that have changed and cases in which they can detect a change has occurred but are not able to recollect what has changed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation